Factors Influencing the Use of Substandard Materials in the Construction of Residential Buildings - Faremi, Olajide Julius; Ajayi, Oluranti Olupolola; Faremi, Olamide Elizabeth (CSID Journal of Infrastructure Development, 2020)
The use of substandard materials for the construction of residential buildings within Lagos metropolis is experiencing a growing concern for both the government and the residents. The construction of half-lived and substandard buildings contributes to negative consequences ranging from rapid deterioration of building elements, premature failures of key building components, and sometimes building collapse. This study attempts to investigate the factors influencing the use of substandard construction materials for the construction of residential buildings in Lagos State. This research collected primary data through a cross-sectional survey of professionals engaged in the construction of buildings and building owners within the study area. Two sets of structured questionnaires were developed and administered to each of the groups of respondents, respectively. The collected data were analysed using descriptive and inferential statistical tools. The results show that factors influencing the use of substandard construction materials for the construction of residential buildings include corruption, use of quacks, contractor’s greed and selfish interests, and client’s financial constraints. The results suggested no significant difference in the perception of contractors and building owners on the factors influencing the use of substandard materials for the construction of residential buildings. The study concludes that the use of substandard building materials for the construction of buildings could cause structural failure, high maintenance costs, incessant building defects, and accelerate deterioration of building elements and components. Building clients suggest to engage professionals and refrain from patronizing quacks.